Comparative ''in vitro'' study on the susceptibility and emergence of mutants resistant to danofloxacin and ciprofloxacin among Staphylococcus aureus isolated from bovine mastitis - Cruz, A. D.; Lopes, CADM; Modolo, JR; Gottschalk, A. F. (Soc Brasileira Microbiologia, 1997)
The antimicrobial susceptibility of danofloxacin was compared in vitro with ciprofloxacin against mastitogenic Staphylococcus aureus. Danofloxacin was more active than ciprofloxacin, showing minimal inhibitory concentrations (MIC90), minimal bactericidal concentrations (MBC90) and MBC/MIC ratio lower than those of ciprofloxacin. Ciprofloxacin-resistant mutants occurred at higher frequencies (greater than or equal to 10(-6)) than for danofloxacin (10(-9)).
Keywords: Staphylococcus aureus; danofloxacin; ciprofloxacin; susceptibility; resistant mutants